Enhancing Indonesian Language Learning Through Brain-Based Learning and Digital Comics: A Quasi-Experimental Study in Elementary Education - Baiq Wigisni Zahrah; Sri Endang Kurniawati; Ni Nyoman Kurnia Wati (Journal of Innovation and Research in Primary Education, 2026)
Low Indonesian language learning outcomes among sixth-grade students at SD Negeri 3 Candikuning, as evidenced by mid-semester summative assessment scores, prompted this investigation. This study examined the effectiveness of Brain Based Learning model assisted by digital comics as an innovative learning tool aligned with brain functioning principles to enhance narrative text comprehension and foundational literacy. Employing a quasi-experimental one-group pretest-posttest design, 24 sixth-grade students participated in a single 105-minute instructional session utilizing digital comics and Brain Based Learning modules. Data collection instruments included observation checklists and written assessments (multiple-choice and essay questions) administered before and after the intervention. Descriptive statistics (mean, standard deviation) and paired samples t-test were employed for data analysis. Results demonstrated substantial improvement, with mean scores increasing from 66.33 to 85.79. The correlation between pretest and posttest scores was exceptionally strong (r = 0.953, p < .001). The paired samples t-test revealed statistically significant differences (t = -16.562, df = 23, p < .001), confirming that Brain Based Learning model assisted by digital comics significantly enhanced Indonesian language learning outcomes. The reduction in standard deviation from 12.51 to 7.59 indicated more equitable learning conditions. These findings validate the integration of neuroscience-based pedagogy with engaging digital media for elementary literacy instruction.